Exploiting the potential of polyphenolic biomordants in environmentally friendly coloration of wool with natural dye from Butea monosperma flower extract. Issue 4 (19th May 2019) - Shahid-ul-Islam,; Rather, Luqman Jameel; Shabbir, Mohd; Sheikh, Javed; Bukhari, Mohd Nadeem; Khan, Mohd Ali; Mohammad, Faqeer
ABSTRACT: Coloration of textiles with natural dyes involves huge consumption of chemicals; mainly, metal salt mordants, which pose serious environmental challenges. To mitigate this pollution, more and more environmentally friendly, biodegradable, biocompatible and renewable products should be popularized in dyeing industry. This paper proposes a sustainable and metal salt-free dyeing of wool samples by employing natural mordants extracted from pomegranate peel ( Punica granatum L), gallnut ( Quercus infectoria L) and catechu ( Acacia catechu ). The color parameters of dyed wool samples were greatly found to be dependent on the chemical compounds present in respective biomordants and their interaction ability with the functional groups of wool and the dye molecules. The investigated biomordants exhibit different interactions with coloring compounds of Butea monosperma (palas) dye resulting in deep brown, olive green, dark brown, cinnamon, burgundy, and yellowish hues on wool. All the biomordants selected in this study improved dye performance and resulted in a broad beautiful spectrum of colors with acceptable fastness properties. The results encourage the search and exploitation of new plant species as a source of biomordants to replace metallic and toxic mordants currently used in textile industry.